2020
DOI: 10.11606/issn.2176-7262.v53i2p127-133
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do contraceptivo hormonal na depressão, ansiedade e qualidade de vida

Abstract: Objetivo: Identificar o efeito do uso de contraceptivos hormonais orais na depressão, ansiedade e qualidade de vida. Métodos: Neste estudo, utiliza-se o método transversal e a amostra foi 113 mulheres em idade reprodutiva. Para avaliação de depressão, ansiedade e qualidade de vida foram utilizados o Inventário de BECK, IDATE Traço-Estado e o SF-36, respectivamente. Para análise estatística utilizou-se o programa STATA 14.0. O nível de significância adotado foi de 5%. Resultados: Mulheres que utilizam contracep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
0
0
Order By: Relevance
“…These differences highlight the need for comprehensive and equitable sexuality education for both sexes 6 . Furthermore, it was shown that there is no harmful relationship between psychological effects and preferences for combined hormonal contraceptives (CHOC), which was a frequent question when it came to contraception, with the conclusion that there are no significant adverse effects in women without comorbidities 8 .…”
Section: Discussionmentioning
confidence: 99%
“…These differences highlight the need for comprehensive and equitable sexuality education for both sexes 6 . Furthermore, it was shown that there is no harmful relationship between psychological effects and preferences for combined hormonal contraceptives (CHOC), which was a frequent question when it came to contraception, with the conclusion that there are no significant adverse effects in women without comorbidities 8 .…”
Section: Discussionmentioning
confidence: 99%